A bibliometrics review of hotspots in water footprint research based on co-words network analysis - Sun, Yun; Wang, Zhibin; Lee, Lien-Chieh; Li, Xinming; Wang, Yuan (Frontiers in Environmental Science, 2022)
The uneven distribution of water resources and production fragmentation make the study of water footprint an important part of water resources management and environmental research. This paper provides a bibliometrics analysis of 3822 papers related to the water footprint topic before 2021, including 2381 English papers from the Science Citation Index (SCI) database and 1441 Chinese papers from the China National Knowledge Infrastructure (CNKI) database. We applied the method of co-word analysis to study the changes in hot research fields in four stages and represented a comparative analysis of highly cited papers and the application of water footprint theory in various sectors. First, water footprint can be divided into two categories: “volumetric” water footprint and “impact-oriented” water footprint. "Volumetric" water footprint methodology focuses on water consumption while "impact-oriented" water footprint methodology focuses more on the environmental impact of water use. Water scarcity, carbon footprint, and grey water are the high-frequency keywords of both two databases. The research linkage of papers related to water footprint from the SCI database has gradually shifted to climate change and carbon emission, while, those from the CNKI database are more closely linked to ecological footprint and sustainable development. Second, SCI's highly cited papers prefer to study the water footprint through scientific experiments from a bottom-up perspective, while CNKI's highly cited papers prefer to combine economics and management theories to study the water footprint from a top-down perspective. In addition, water footprint theory is mainly applied in agriculture and industrial sectors and less in service sectors. This paper provides a review of water footprint research on a large scale and a reference for future research on water footprint.